"Crossfire Couples: Agency and Marginality in the Lives of Okinawan Women in Relationships with American Military Men." - Ames, Christopher (Abstracts of the Annual Meeting of the Japanese Society of Cultural Anthropology, 2008)
Okinawan women in relationships with U.S. military men face discrimination from community members concerned about social problems rightly or wrongly associated with international romance. These women are subject to discrimination on both sides base fences. However, as the actions of my Okinawan female informants demonstrate, they are not passive victims, but are agents resisting the politicization of their love lives.